On the Estimation of Zooplankton-Mediated Active Fluxes in Oxygen Minimum Zone Regions - Kiko, Rainer; Hauss, Helena (Frontiers in Marine Science, 2019)
In the Peruvian upwelling system, the mesopelagic oxygen minimum zone (OMZ) is the main vertically structuring feature of the pelagic habitat. Several zooplankton and nekton species undertake diel vertical migrations (DVMs) into anoxic depths. It has been argued that these migrations contribute substantially to the oxygen consumption as well as excretion of dissolved compounds (in particular ammonium) in subsurface waters. However, metabolic suppression as a response to low ambient oxygen partial pressure ($pO_2$) has not been accounted for in these estimates. Here, we present estimates of zooplankton- and nekton-mediated oxygen consumption and ammonium release based on vertically stratified net hauls (day/night, upper 1000m). Samples were scanned, followed by image analysis and size-/taxon-specific estimation of metabolic rates of all identified organisms as a function of their biomass as well as ambient temperature and $pO_2$. The main crustacean migrants were euphausiids (mainly E. mucronata) on offshore stations and the commercially exploited squat lobster Pleuroncodes monodon on the upper shelf, where it often undertakes migration to the seafloor during the day. Correction for metabolic suppression results in a substantial reduction of both respiration and ammonium excretion within the OMZ core. Ignoring this mechanism leads to tenfold higher estimate of DVM-mediated active export of carbon by respiration to below 100 m depth at deep-water stations. The DVM-mediated release of ammonium by euphausiids into the 200 to 400 m depth layer ranges between $0$ and $36.81\ μ mol\ NH_4\ m^{-2} d^{-1}$, which is insufficient to balance published estimates of ammonium uptake rates due to anammox. It seems critical to account for the modulation of zooplankton metabolic activity at low oxygen in order to correctly represent the contribution of migrating species to the biological pump.